"\\sqrt{f(x)}" have the same zeros as "f(x)" and it determining for "x \\geqslant -1". Moreover, "y'=-\\frac{f'(x)}{2\\sqrt{f(x)}}" so we have "y \\uparrow, -1<x<-1\/3, x>1; \\,\\, y \\downarrow -1\/3<x<1". And we see that at "x=-1: \\,\\, y' \\to \\infty", so we have vertical tangent. And at "x \\to 1 \\pm: \\,\\,y'= \\pm \\sqrt{2}", i.e. parts of function have "90^{\\circ}" angle between each other and "45^{\\circ}" and "135^{\\circ}" between "x"-axis (from right to left).
"y=-\\sqrt{f(x)}" is given by symmetric mapping of "y=\\sqrt{f(x)}" with respect to "x"-axis.
Comments
Leave a comment